Factors affecting the acceptance of Near Field Communication enabled mobile payments : an empirical study of Pakistan - Brohi, Imtiaz Ali (Kulliyyah of Information and Communication Technology, International Islamic University Malaysia, 2019)
Near field communication is short range contactless communication technology that has made users life convenient around the world by offering mobile payment, digital content exchange and connecting electronic devices with a simple touch or wave. Smartphone technology has brought a new change in our lifestyle whether it is connecting with the world, monitoring self-fitness and undertaking monetary transactions. Within the domain of smartphone, the most recent promising technology development is Near Field Communication (NFC) that has changed the approach of consumers in Mobile Payment (MP) system. NFC enabled payment system acceptance tendency in developing country such as Pakistan is at slow pace comparing to other developing countries where people are using smartphones as a wallet. The purpose of this study is to investigate and identify the significant factors that affect consumer's behavioural intention to use NFC MP. This study proposed a model to measure the behavioural intention to use NFC MP in Pakistan. In this study, constructs such as Performance Expectancy (PE), Effort Expectancy (EE), Social Influence (SI), Facilitating Conditions (FC), Hedonic Motivation (HM), Habit, Compatibility, Personal Innovativeness in Information Technology (PIIT), Risk, and NFC Payment Knowledge (NFCPK) are measured. The hypothetical relationships were examined through Structural Equation Modelling (SEM) using Smart-PLS software. Quantitative methodology (survey questionnaire) is used to investigate the correlational paths between constructs. Using a cluster sampling approach, a total of 409 responses were collected from smartphone users. Research findings show that 10 out of 13 hypotheses were found to be statistically significant, leaving 3 as insignificant. The findings revealed that 62.6% variance in behavioural intention is explained by PE, EE, FC, HM, Habit, Compatibility, Risk and NFC PK. Similarly, 45.2% variance in use behaviour is explained by behavioural intention, FC, and Habit. Furthermore, Risk factor involved in adoption and use of NFC MP have a negative correlation with behavioural intention. Thus, Risk was considered as an obstacle in the acceptance and use of NFC MP. This study expands the use of Extended Unified Theory of Acceptance and Use of Technology (UTAUT2) in Information System (IS) research, extends and validates the UTAUT2 model within the NFC MP context. Moreover, the findings of this research are valued to the stakeholders interested in developing and implementing NFC MP. Potential stakeholders would benefit from an improved and revised understanding of these aspects. The identification of important factors influencing NFC MP in this study will assist them to develop and implement their system to ensure the full acceptance and use of the NFC MP.